2013
DOI: 10.1371/journal.pone.0065983
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Melanocytes Obtained from the Skin Ameliorates Apomorphine-Induced Abnormal Behavior in Rodent Hemi-Parkinsonian Models

Abstract: Tyrosinase, which catalyzes both the hydroxylation of tyrosine and consequent oxidation of L-DOPA to form melanin in melanocytes, is also expressed in the brain, and oxidizes L-DOPA and dopamine. Replacement of dopamine synthesis by tyrosinase was reported in tyrosine hydroxylase null mice. To examine the potential benefits of autograft cell transplantation for patients with Parkinson’s disease, tyrosinase-producing cells including melanocytes, were transplanted into the striatum of hemi-parkinsonian model rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A recent report studying α‐syn behavior in SK‐MEL‐28 proposes that the transfer of α‐syn from melanoma to neuronal cells may affect the pathogenesis of PD (Lee et al 2013a). Interestingly, the transplantation of tyrosinase‐positive melanocytes in rat models of PD has been shown to have beneficial effects and further argues for the need to explore α‐syn behavior in melanoma (Asanuma et al 2013). The presence of higher molecular weight species of α‐syn in SK‐MEL‐28 and the differential localization of the two forms of α‐syn makes SK‐MEL‐28 a good model to evaluate the formation and existence of non‐toxic oligomers and to investigate if these higher order structures have any physiological significance under normal cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report studying α‐syn behavior in SK‐MEL‐28 proposes that the transfer of α‐syn from melanoma to neuronal cells may affect the pathogenesis of PD (Lee et al 2013a). Interestingly, the transplantation of tyrosinase‐positive melanocytes in rat models of PD has been shown to have beneficial effects and further argues for the need to explore α‐syn behavior in melanoma (Asanuma et al 2013). The presence of higher molecular weight species of α‐syn in SK‐MEL‐28 and the differential localization of the two forms of α‐syn makes SK‐MEL‐28 a good model to evaluate the formation and existence of non‐toxic oligomers and to investigate if these higher order structures have any physiological significance under normal cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…6) Tyrosine hydroxylase : Vitiligo is a frequent autoimmune disease characterized by an immune-mediated destruction of melanocytes leading to skin depigmentation 114 . Interestingly, the biochemical pathways allowing the synthesis of melanin and dopamine respectively present major similarities 115 , 116 , and the intra-CNS grafting of melanocytes was recently proposed as a therapeutic approach for Parkinson's disease, a neurodegenerative disorder affecting dopaminergic neurons 115 . In this regard, tyrosine hydroxylase, a major enzyme of the dopamine synthesis pathway in neurons is also essential to melanin synthesis and is targeted by autoantibodies in vitiligo 117 , 118 .…”
Section: The Cns Is a Major Source Of Superautoantigensmentioning
confidence: 99%
“…In fact, supplement of DA synthesis by tyrosinase has been reported in TH (Tyrosine Hydroxylase) null mice [14]. Further, it was shown earlier by [15] that transplantation of a non-melanogenic cells transfected with tyrosinase gene, as tyrosinase-producing cells, which constitutively produce L-DOPA, resulted in marked amelioration of the asymmetric apomorphine-induced rotation in hemi-parkinsonian mice lesioned with 6-hydroxydopamine (6-OHDA). In an another experiment they have also shown that transplantation of melanocytes from the back skin of black newborn mice, but not from albino mice, showed marked improvement in the apomorphine-induced rotation behavior.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the most common therapy uses the drug levodopa, a substrate of dopamine (DA) which is associated with motor skills [31]. Since melanocytes contain Tyrosinase which can synthesize DOPA from Tyrosine, it appears that transplantation of melanocytes can be a better substitute for DOPA therapy than Levodopa administration for PD patients [15]. Levodopa administration to PD patients while a continuous treatment and a palliative, transplantation of melanocytes could be onetime and the cells will supply DOPA regularly as when needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation